PENGARUH PEMBELAJARAN MEDIA YOUTUBE TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN AKIDAH AKHLAK KELAS VII MADRASAH TSANAWIYAH. MUHAMMADIYAH 12 PALIRANGAN SOLOKURO LAMONGAN TAHUN PELAJARAN 2023/2024 - Ernawati; Idzi layyinnati (STIT Muhammadiyah Paciran, 2023)
The current development of technology has led to media no longer being seen merely as a tool for educators, but also as an important means to achieve educational goals more effectively and efficiently. Media can represent educators in certain matters with greater precision, clarity, and appeal. Along with the advancement of science and technology, efforts are being made to create quality individuals. One way to improve the quality of individuals is by enhancing the quality of education, which can be achieved by updating the existing curriculum. From the observations at Madrasah Tsanawiyah Muhammadiyah 12 Palirangan and interviews with seventh grade students, it was found that the lack of media related to learning materials also leads to monotonous teaching, resulting in students being less motivated to receive and understand the material, as well as a lack of creativity from educators in utilizing technological media. Every lesson should incorporate innovative learning methods that can encourage students to be active and enthusiastic in their studies.